The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1172/jci.insight.88226
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced FCGR2A and FCGR3A signaling by HIV viremic controller IgG

Abstract: HIV-1 viremic controllers (VC) spontaneously control infection without antiretroviral treatment. Several studies indicate that IgG Abs from VCs induce enhanced responses from immune effector cells. Since signaling through Fc-γ receptors (FCGRs) modulate these Ab-driven responses, here we examine if enhanced FCGR activation is a common feature of IgG from VCs. Using an infected cell-based system, we observed that VC IgG stimulated greater FCGR2A and FCGR3A activation as compared with noncontrollers, independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…Although the role of the Fc receptors in virus control remains to be thoroughly explored, one can speculate that the downregulation of these receptors could be associated with both lower activation/inflammation and the HIV reservoir observed in HIC compared to cART-treated individuals (40). It was also reported that the quality rather than the quantity of FCGR signaling could be responsible for the wider polyfunctional Fcmediated responses observed in HIC (36,41). In parallel, there is a downregulation in HIC of mitogen-activated protein kinase 1 (MAPK1) and PI3-kinase (PIK3CG and PIK3CB); both are critical regulatory factors of immune stimulation and suppression during inflammation (15,16,42).…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of the Fc receptors in virus control remains to be thoroughly explored, one can speculate that the downregulation of these receptors could be associated with both lower activation/inflammation and the HIV reservoir observed in HIC compared to cART-treated individuals (40). It was also reported that the quality rather than the quantity of FCGR signaling could be responsible for the wider polyfunctional Fcmediated responses observed in HIC (36,41). In parallel, there is a downregulation in HIC of mitogen-activated protein kinase 1 (MAPK1) and PI3-kinase (PIK3CG and PIK3CB); both are critical regulatory factors of immune stimulation and suppression during inflammation (15,16,42).…”
Section: Discussionmentioning
confidence: 99%
“…(D) Tetherin-high antibody binding assay indicates binding of the indicated antibody in the presence of the indicated drug, NF279 (left) or NF449 (right). Binding index (BI) was calculated for each anti-HIV antibody by multiplying the percent Ab binding within the entire HIV ϩ population against the MFI ratio of HIV-positive over HIV-negative cells (56,57). Results are the means Ϯ SEMs from at two or three independent experiments.…”
Section: Nf279 and Nf449 Block Hiv-1 Productive Infection In A Dose-dmentioning
confidence: 99%
“…To further explore the hypothesis that NF279 and NF449 activities are dependent on direct binding to the HIV-1 Env V1V2 region, the PG9 binding site, we employed a well-characterized antibody binding system that retains viral particles on the surface of HIV-infected CD4 ϩ T cells (55)(56)(57). This system is based on high expression of tetherin on cells, which allows for the enhanced resolution of differences in antibody binding.…”
Section: Nf279 and Nf449 Block Hiv-1 Productive Infection In A Dose-dmentioning
confidence: 99%
See 2 more Smart Citations